A Novel 360° Framework for Developing a Graduate as a Whole Person by Enhancing the Affective Domain Skills - Evelyn Brindha, V.; Beulah Christalin Latha, C. (Journal of Engineering Education Transformations, 2025)
“It takes more than intelligence to act intelligently”. An education that enriches and kindles the thinking ability of a person and ignites not only the knowledge but also the skills and attitude to draw to an innovative conclusion with holistic development is termed Whole Person Education (WPE). A framework for achieving a 360-degree development of a student is devised and used. This framework consists of 14 indicators that are mapped with the Graduate Attributes (GA) defined by NBA. These 14 indicators include research, advanced studies, industry interactions, publications, IPR, sports, and other life skills such as communication, leadership skills, teamwork, and character building.